Multicylinder Engine Shaking Forces and Moments - Samuel Doughty (IPTEK The Journal for Technology and Science, 2016)
The dynamic forces and moments arising from the motion of internal components in IC engines are known as Shaking Forces and Shaking Moments. Thes forces and moments are transmittted directly  to the supporting  structure,  whether  it be a concrete  block or a ship's  frame. They can cause significant damage if not properly evaluated at the design stage. It should be noted that these are inertial reactions only, and are unaffected by cylinder firing pressure.  By a driect appeal to fundamental momen- tum principles, this paper presents an elegant and completely general approach to their determination, based on fundamental momentum principles.  This is much more simple than the conventional direct approach through the piece-by-piece application of Newton's Second Law